Reconstrução curricular em educação física no ensino médio: um diálogo com jovens de uma escola da Rede Estadual de Educação de Minas Gerais - Tábata Aline Januario (2021)
This dissertation has as object of investigation my pedagogical practice, as a Physical Education teacher, in a junior high school of the Minas Gerais State, called "Escola de Baixo" (real name withheld). The study had as its main objective to reconstruct my curricular proposal for the teaching of this subject in this school in constant discussion with young students. From this central objective, the following specific objectives were: to analyze the trajectory of the Physical Education curriculum organization developed by the researcher; expand my knowledge of the socio-cultural reality of young students at the “Escola de Baixo”; Get to know more deeply the demands and the learning needs in this subject; to promote greater participation of the students in the decision-making process about the curricular actions of the content at the school in question; to prepare a curricular proposal for the teaching of the subject for the three years of high school at the institution. The inquiry draws on the contributions of critical theories in School Physical Education in Brazil (BRACHT, 1992; GONZALEZ AND FENSTENSEIFER, 2009), on teaching planning (RAYS, 1989), on curriculum theories (PEREZ GOMEZ; SACRISTAN, 2007), and from the field of studies on youth and the youth condition in Brazilian society (DAYRELL, 2007). The analysis is of qualitative nature and used the methodological resources of the research-action of Thiollent (2009).The investigation used the following research instruments: the application of a questionnaire to all high school students, a semi-structured interview with a group of eight young students, and the collective dialogue with the students of the second year of high school, carried out through a data collection instrument called in the research “Café com Papo” (Coffee and chat). The research allowed a reflective reading about my curricular practice, more specifically, the precarious ways of organizing my teaching planning; the submission relationships due to the demands arising from school management; the mistakes made while interacting with the young students from that school; my strategies used for legitimizing content, which overvalued extracurricular actions when compared to the curricular actions; a more accurate reading of my own gaps in professional training; and also a better understanding of the sociocultural reality of my young students and the clarification of the existing connections between this reality and the teaching of Physical Education at school.